André Kertész and Avant Garde Photography of the Twenties and Thirties. - Ford, Colin; Juda, Annely; Juda, David (London : Annely Juda Fine Art, 1999)
Kertesz, André ; Berman, Mieczyslaw ; Biermann, Aenne ; Blossfeldt, Karl ; Blumenfeld, Erwin ; Bourke-White, Margaret ; Brancusi, Constantin ; Bruehl, Anton ; Dubreuil, Pierre ; Feininger, T. Lux ; Lissitzky, El ; Man Ray ; Miller, Lee ; Moholy-Nagy, Laszlo ; Outerbridge, Paul ; Paladino, Vinicio ; Rodchenko, Alexander ; Schneeberger, Adolf ; Stieglitz, Alfred ; Vordemberge-Gildewart, Friedrich ; Weidemeyer, Carl ; Weston, Edward ; Zwart, Piet
biog.
Engels
André Kertész and Avant Garde photography of the twenties and thirties, Annely Juda Fine Art, London, 25 February - 10 April 1999
boek